Tafsir Tarbawi: Perspective KH. Mishbah Musthafa about Islamic Education Values in QS. al-Inshirah - Takrip, Muhammad; Zulfikar, Eko (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2023)
This article aims to analyze tarbawi's interpretation of the values of education in QS. al-Inshirah. The focus of his research is directed at the interpretation of Mishbah Mushtafa in his book of interpretation al-Iklil which has Javanese nuances. By using the thematic method and content analysis, it was concluded that: First, QS. al-Inshirah is the 94-th letter in the Qur'an. In accordance with its name al-Insyirah, this letter contains an explanation of the courage of the Prophet Muhammad SAW for the harsh rejection of the polytheists for the da'wah he delivered so that the Prophet was victorious. Second, although in general QS. al-Inshirah talksabout the story of the Prophet Muhammad against the polytheists, but in it there are educational values that should be instilled in the souls of all Muslims.There are at least six educational values in the QS. al-Inshirah which is extracted from the interpretation of Mishbah Mushtafa in his commentary book al-Iklil, namely the value of openness, the value of morals, the value of effort (effort), the value of perseverance and perseverance, the value of patience, and the value of monotheism.